2020
DOI: 10.3390/su12041464
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Reference Framework for Enterprise Resilience Enhancement

Abstract: Enterprise resilience is a key capacity to guarantee enterprises' long-term continuity. This paper proposes the enterprise resilience Conceptual Reference Framework to characterize enterprise resilience capacity. The framework is composed of 71 disruptive events that enterprises consider as endangerments to their continuity. The framework also comprises constituent capabilities of enterprise resilience in terms of preparedness and recovery capabilities and elements that support the transition from the AS IS si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 55 publications
1
42
0
2
Order By: Relevance
“…For the purpose of risk mitigation, and post-disaster stabilization, an assessment protocol incorporating the SCRAMTM analytic tool (Supply Chain Resilience Assessment and Management tool) [165] for measuring the resilience by detecting the association between an organization's vulnerabilities and capabilities can be applied. Many research efforts were made to examine and improve crisis response strategies [166], by assessing organizations' vulnerability [167].…”
Section: Discussion Of Enterprise Actions During the Covid-19 Pandemicmentioning
confidence: 99%
“…For the purpose of risk mitigation, and post-disaster stabilization, an assessment protocol incorporating the SCRAMTM analytic tool (Supply Chain Resilience Assessment and Management tool) [165] for measuring the resilience by detecting the association between an organization's vulnerabilities and capabilities can be applied. Many research efforts were made to examine and improve crisis response strategies [166], by assessing organizations' vulnerability [167].…”
Section: Discussion Of Enterprise Actions During the Covid-19 Pandemicmentioning
confidence: 99%
“…Literature studies on crisis in an organization relate little to the aspects of the relational capital of a company. It should be noted that while the literature on crisis management abounds in research concerning determinants of companies' resilience to crisis [28][29][30][31][32], it rarely points to the importance of relational capital as a medium in anti-crisis processes. Based on the above, the research gaps observed brought the author to indicate the relational capital of a company as an important, although not well-recognized or appreciated factor impacting the resilience of a company to crisis events.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, just as individual companies are building resilient supply chains [238][239][240][241][242], an industrial civilization needs to consider the benefits of resilience. Similarly, just as individual enterprises are undertaking preventative actions to be more resilient in the face of a disruptive event [243], so can the entire industrial base become more prepared and resilient. Preparedness capacity in this context means being flexible and agile enough to anticipate the consequences of a pandemic such as COVID- 19 and promote the open source paradigm before the next pandemic occurrence.…”
Section: Discussionmentioning
confidence: 99%